The Effect of Flexible Working Arrangements and Work-Life Balance on Job Performance With Employee Engagement As an Intervening Variable (Case Study of The Deputy For Industry and Investment) - Siti Safaria; Alief Nurunnahdliyah (Winter Journal: IMWI Student Research Journal, 2026)
This study is motivated by the fluctuation in pension fund investment returns in Indonesia despite the continuous growth in total assets and investment value. The study aims to examine the effect of asset allocation strategies on pension fund investment returns and to test the moderating role of interest rates. The study employs secondary data for the period 2020–2024 obtained from pension fund financial statements and the Bank Indonesia policy rate. The sample consists of 35 pension funds with 175 observations selected using purposive sampling. Data were analyzed using panel data regression and moderation testing. The results indicate that deposits, government securities, and equities have no significant effect on investment returns, while corporate bonds have a positive and significant effect. Interest rates are found to strengthen the relationship between asset allocation and pension fund investment returns.